Genome-wide identification of Shaker K+ channel family in Nicotiana tabacum and functional analysis of NtSKOR1B in response to salt stress - Yuan, Guang; Nong, Tongjia; Hunpatin, Oluwaseyi Setonji; Shi, Chuhan; Su, Xiaoqing; Xu, Fangzheng; Wang, Yihui; Zhang, Zhaoting; Ning, Yang; Liu, Haobao; Wang, Qian (Frontiers in Plant Science, 2024)
Soil salinization poses a mounting global ecological and environmental threat. The identification of genes responsible for negative regulation of salt tolerance and their utilization in crop improvement through gene editing technologies emerges as a swift strategy for the effective utilization of saline-alkali lands. One efficient mechanism of plant salt tolerance is maintaining the proper intracellular K+/Na+ ratio. The Shaker K+ channels play a crucial role in potassium absorption, transport, and intracellular potassium homeostasis in plant cells. Here, the study presents the first genome-wide identification of Shaker K+ channels in Nicotiana tabacum L., along with a detailed bioinformatic analysis of the 20 identified members. Transcriptome analysis revealed a significant up-regulation of NtSKOR1B, an outwardly-rectifying member predominantly expressed in the root tissue of tobacco seedlings, in response to salt stress. This finding was then confirmed by GUS staining of ProNtSKOR1B::GUS transgenic lines and RT-qPCR analysis. Subsequently, NtSKOR1B knockout mutants (ntskor1) were then generated and subjected to salt conditions. It was found that ntskor1 mutants exhibit enhanced salt tolerance, characterized by increased biomass, higher K+ content and elevated K+/Na+ ratios in both leaf and root tissues, compared to wild-type plants. These results indicate that NtSKOR1B knockout inhibits K+ efflux in root and leaf tissues of tobacco seedlings under salt stress, thereby maintaining higher K+/Na+ ratios within the cells. Thus, our study identifies NtSKOR1B as a negative regulator of salt tolerance in tobacco seedlings.